2022
DOI: 10.1371/journal.pone.0274965
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence, bullying, burnout, job satisfaction and their correlation with depression among Bangladeshi nurses: A cross-sectional survey during the COVID-19 pandemic

Abstract: Background Depression is one of the most serious yet understudied issues among Bangladeshi nurses, bringing health dangers to this workforce. This study aimed to investigate how workplace violence (WPV), bullying, burnout, and job satisfaction are correlated with depression and identify the factors associated with depression among Bangladeshi nurses. Methods For this cross-sectional study, data were collected between February 26, 2021, and July 10, 2021 from the Bangladeshi registered nurses. The Workplace V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 72 publications
6
39
0
Order By: Relevance
“…Consistent with previous studies that the level of burnout among HPs had worsened with the pandemic prolonged ( Chowdhury et al, 2022 , Prasad et al, 2021 , Kuriyama et al, 2022 ), this study found that the prevalence of burnout (EE, and DPA) in HPs at a high level persistently during the three years of the pandemic. To date, this is the first study that sustained monitored the burnout of health professionals in China.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies that the level of burnout among HPs had worsened with the pandemic prolonged ( Chowdhury et al, 2022 , Prasad et al, 2021 , Kuriyama et al, 2022 ), this study found that the prevalence of burnout (EE, and DPA) in HPs at a high level persistently during the three years of the pandemic. To date, this is the first study that sustained monitored the burnout of health professionals in China.…”
Section: Discussionsupporting
confidence: 91%
“…We found a significant correlation between the COVID-19-BS and levels of depression and anxiety. Although there is a lack of studies searching the relationship between burnout and depression and anxiety in the general population during the pandemic, several studies support the correlation between these variables among healthcare workers, teachers, police officers and students (Chowdhury et al, 2022; Ghio et al, 2021; Hung & Liu, 2022; Karakose et al, 2022; Tehrani, 2022; Tomaszek & Muchacka-Cymerman, 2022; Ulfa et al, 2022). In addition, Yıldırım and Solmaz (2022) found that COVID-19 stress predicted COVID-19 burnout in a sample of Turkish adults (Yıldırım & Solmaz, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The whole recruitment process is presented in Fig. 1 , which was published elsewhere in an article from the same project [ 49 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%